The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.1038/s41598-023-32031-7
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of non-household contacts during the COVID-19 pandemic in 2020 and 2021 in the Netherlands

Abstract: The COVID-19 pandemic was in 2020 and 2021 for a large part mitigated by reducing contacts in the general population. To monitor how these contacts changed over the course of the pandemic in the Netherlands, a longitudinal survey was conducted where participants reported on their at-risk contacts every two weeks, as part of the European CoMix survey. The survey included 1659 participants from April to August 2020 and 2514 participants from December 2020 to September 2021. We categorized the number of unique co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…The PiCo survey was held three times per year among a representative sample of the population in the Netherlands [3,39]. The CoMix survey was held every two weeks on a selected internet panel [40,41]. The 70+ participants in the PiCo and CoMix surveys reported 2.3 (2.1 - 2.5) (mean and 95% bootstrap CI) and 2.5 (2.0 - 3.1) contacts per day around survey period 1 and 5.1 (4.7 - 5.5) and 4.8 (2.1 - 10.2) contacts per day around survey period 2.…”
Section: Discussionmentioning
confidence: 99%
“…The PiCo survey was held three times per year among a representative sample of the population in the Netherlands [3,39]. The CoMix survey was held every two weeks on a selected internet panel [40,41]. The 70+ participants in the PiCo and CoMix surveys reported 2.3 (2.1 - 2.5) (mean and 95% bootstrap CI) and 2.5 (2.0 - 3.1) contacts per day around survey period 1 and 5.1 (4.7 - 5.5) and 4.8 (2.1 - 10.2) contacts per day around survey period 2.…”
Section: Discussionmentioning
confidence: 99%
“…All analyses are performed in R version 4.1.3 25 using the mgcv package 26 with family ocat for ordered categorical variables. Code is available on Github 27 , and data is published on Zenodo 28 in the standardised format of socialcontactdata . org .…”
Section: Methodsmentioning
confidence: 99%
“…The datasets analysed in the current study are available in the Zenodo repository (https://doi.org/10.5281/zenodo.4790347) 28 under CC BY 4.0 license.…”
Section: Data Availabilitymentioning
confidence: 99%
“…Face-to-face and physical contacts between members of different households were to be reduced, as each contact could be an at-risk event for transmission. Many contact surveys that were conducted during the pandemic showed that more stringent COVID-19 measures indeed lead to lower contact rates [1][2][3][4][5][6][7][8]. Most contact-reducing measures were lifted shortly after the emergence of the more transmissible Omicron variants of SARS-CoV-2 in late 2021.…”
Section: Introductionmentioning
confidence: 99%